2019
DOI: 10.1155/2019/6706590
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Image Thresholding Method Based on Subspace Elimination Optimization

Abstract: Multilevel thresholding is to find the thresholds to segment the image with grey levels. Usually, the thresholds are so determined that some indicator functions of the segmented image are optimized. To improve the computational efficiency, we presented an optimization method for multilevel thresholding. First, the solution space is divided into subspaces. Second, the subspaces are searched to obtain their current local optimal value. Third, the subspaces that are of worse current optimal value are eliminated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…They concluded that compared to traditional methods, the QPSO improved both accuracy and speed. Qin et al [60] employed the subspace elimination optimization (SSEO) for MLT image segmentation. They applied the SSEO for four different images, and they compared it to the particle swarm optimization (PSO).…”
Section: Related Workmentioning
confidence: 99%
“…They concluded that compared to traditional methods, the QPSO improved both accuracy and speed. Qin et al [60] employed the subspace elimination optimization (SSEO) for MLT image segmentation. They applied the SSEO for four different images, and they compared it to the particle swarm optimization (PSO).…”
Section: Related Workmentioning
confidence: 99%
“…Although numerous effective threshold segmentation algorithms are in use, traditional methods may struggle to meet the requirements of more detailed and precise segmentation, making multidimensional threshold segmentation more suitable for efficient targeting of images. In 2019, Qin et al proposed a multi-level thresholding method for images based on subspace elimination optimization [4]. Zhao et al introduced a chaos-randomized ant colony optimization approach, employing two-dimensional maximum entropy for multi-threshold image segmentation [5].…”
Section: Introductionmentioning
confidence: 99%